Agronomic characterization of high-yielding irrigated barley accessions in the Cerrado - Sayd, Ricardo Meneses; Amabile, Renato Fernando; Faleiro, Fábio Gelape; Montalvão, Ana Paula Leite; Coelho, Mateus Costa (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to estimate the genetic, phenotypic, and environmental parameters of 113 barley accessions (Hordeum vulgare), previously selected based on high yield, in an irrigated production system in the Cerrado (Brazilian savanna), for use in breeding programs in Brazil. The experiment was conducted in 2013 at two sites in the Federal District, using a randomized complete block design with three replicates. The evaluated traits were: grain yield, kernel plumpness, thousand grain weight, plant height, lodging, and days to heading. Significant differences were observed between environment and accessions for all studied traits, as well as genotype x environment interaction. The MCU 3832 PI 402310, MCU 3484 PI 401962, CI 08053 Custer, MCU 3634 PI 402112, and MCU 3816 PI 402294 accessions stood out regarding grain yield and kernel plumpness. It is possible to obtain high selection gains with high heritability values. However, indirect selection is not recommended in the experimental conditions due to the low genotypic and phenotypic correlations obtained. It is also possible to select barley accessions with high yield and early heading date simultaneously, an important factor in the genotype selection process for future experiments. The accessions from Colombia are the most adapted to the Cerrado conditions.